2014
DOI: 10.1371/journal.pone.0096053
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of IL-6 by Hepatocytes Is a Normal Response to Common Hepatic Stimuli

Abstract: Exogenous interleukin 6 (IL-6), synthesized at the initiation of the acute phase response, is considered responsible for signaling hepatocytes to produce acute phase proteins. It is widely posited that IL-6 is either delivered to the liver in an endocrine fashion from immune cells at the site of injury, or alternatively, in a paracrine manner by hepatic immune cells within the liver. A recent publication showed there was a muted IL-6 response in lipopolysaccharide (LPS)-injured mice when nuclear NFκB was speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 39 publications
6
78
1
Order By: Relevance
“…It is known that, in the liver, IL-6 is secreted by Kupffer cells and hepatocytes (35,36). IL-6 induces the production of acute-phase proteins during acute inflammation in the liver, and serum levels of IL-6 correlate positively with the severity of the disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that, in the liver, IL-6 is secreted by Kupffer cells and hepatocytes (35,36). IL-6 induces the production of acute-phase proteins during acute inflammation in the liver, and serum levels of IL-6 correlate positively with the severity of the disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for these results is that the authors did not evaluate the role of donor gene polymorphisms in HCC recurrence [39]. Norris et al showed that hepatocytes could directly synthesize IL6 mRNAs and protein following hepatic stimuli, including partial hepatectomy [40]. Circulating tumor cells can lead to recurrence and metastasis of HCC after liver transplantation [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, under inflammatory conditions some hepatocytes express MHC class II [30] and initiate an adoptive immune response. Hepatocytes produce IL-6 upon stimulation by HGF, lipopolysaccharide, or bacterial hepatotoxins [37] .…”
Section: Hepatocytesmentioning
confidence: 99%